PENGARUH PENERAPAN GOOD GOVERNANCE DAN BUDAYA ORGANISASI TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI PEMEDIASI - MEIDYLISA PATTY (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2019)
This research aims to determine the influence of the implementation of good governance and organizational culture to the quality of financial statements with the transformational leadership as a variable of intervening both partially and simultaneously. This type of research is explanatory research. This research was conducted in 34 regional government working unit (SKPD) Ambon City. Data collection is done by spreading questionnaires, interviews and documentation. The research instruments were tested in advance with Spearman’s validity test and Cronbach Alpha reliability test. The data analysis method used is Path analysis. The results of the research and hypothesis testing showed that the implementation of good governance and organizational culture both directly and indirectly through transformational leadership did not significantly affect the quality of financial statements both partially and simultaneously.